Cladosporium omanense, a new endophytic species from Zygophyllum coccineum in Oman - Halo, Boshra A.; Maharachchikumbura, Sajeewa S.n.; Al-Yahyai, Rashid A.; Al-Sadi, Abdullah M. (Phytotaxa, 2019)
The genus Cladosporium is cosmopolitan in distribution and can be isolated from various sources including plants as endophytes. A strain of Cladosporium was isolated from living leaves of Zygophyllum coccineum in a desert habitat in Oman. Phylogenetic analysis based on the combined internal transcribed spacer (ITS), partial translation elongation factor 1-alpha (TEF) and partial actin (ACT) sequence data shows that this is a novel species, which groups with Cladosporium sphaerospermum complex. The new species is introduced as Cladosporium omanense and is described, illustrated and compared with other known species in the genus. Cladosporium omanense differs from its phylogenetically related species C. endophyticum by its fast growing colonies, longer macronematous and micronematous conidiophores, thickened-walled conidia with conspicuously protuberant shrivelling surface ornamentations.